(3cJGH GdfJa aj Gdabgs - (3CHh YHO Gddg GdbGSe Hf GdMSjf GdZRfhjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf HGH GdejGg EYde CQTOc Gddg Cf GdeGA Ydi hLgjf eWdb hebjO aCeG GdeWdb aYdi SHYI ChLg CMOgG eG jfRd ef GdSeGA hGdKGfi eG jNQL ef GdCQV hGdKGdK GdQGcO s
(3BNQgG (B:s
(3jfJgi HcJGH GdSGHb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddeNWhWg HGdCHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs